Study of users of the communities Jardines 1 and Jardines 2 attended by the Children's Library "Miriam Álvarez Brenes" Heredia, Costa Rica - Barboza Jiménez, Lucrecia (2008)
This document describes the process that was carried out to know the information needs of the real and potential users of the communities Jardines Universitarios 1 and Jardines Universitarios 2 that the "Miriam Álvarez Brenes" Children's Library of the National University attends. It also presents the conclusions and recommendations generated by the study of users, as well as the updated characterization of the target communities contemplated in the study.